Two-Sample Mendelian Randomization Analysis Investigates Causal Associations Between Gut Microbial Genera and Inflammatory Bowel Disease, and Specificity Causal Associations in Ulcerative Colitis or Crohn’s Disease - Liu, Bin; Ye, Ding; Yang, Hong; Song, Jie; Sun, Xiaohui; Mao, Yingying; He, Zhixing (Frontiers in Immunology, 2022)
Background: Intestinal dysbiosis is associated with inflammatory bowel disease (IBD). Besides, ulcerative colitis (UC) and Crohn’s disease (CD), two subtypes of IBD, are characterized by unique microbial signatures, respectively. However, it is unclear whether UC or CD has a specific causal relationship with gut microbiota. Objective: To investigate the potential causal associations between gut microbial genera and IBD, UC, or CD, two-sample Mendelian randomization (MR) analyses were conducted. Materials and Methods: We obtained genome-wide association study (GWAS) summary statistics of gut microbiota and IBD, UC, or CD from published GWASs. Two-sample MR analyses were performed to identify potential causal gut microbial genera for IBD, UC, and CD using the inverse-variance weighted (IVW) method. Sensitivity analyses were also conducted to validate the robustness of the primary results of the MR analyses. Finally, a reverse MR analysis was performed to evaluate the possibility of reverse causation. Results: Combining the results from the primary and sensitivity analyses, six bacterial genera were associated with the risk of IBD, UC, or CD in the IVW method. Briefly, Eubacterium ventriosum group was associated with a lower risk of IBD (P=0.011) and UC (P=1.00×10-4), whereas Coprococcus 2 was associated with a higher risk of IBD (P=0.022) and UC (P=0.007). In addition, we found a positive association of Oxalobacter with IBD (P=0.001) and CD (P=0.002), and of Ruminococcaceae UCG014 with IBD (P=0.005) and CD (P=0.007). We also noticed a negative association between Enterorhabdus (P=0.044) and IBD, and between Lachnospiraceae UCG001 (P=0.023) and CD. We did not find casual effects of IBD, UC, or CD on these bacterial genera in the reverse MR analysis. Conclusion: This study expanded gut microbial genera that were causally associated with the risk of IBD, and also revealed specificity-gut microbial genera for UC or CD.